Pengaruh Sektor Pariwisata Terhadap Penyerapan Tenaga Kerja Di 9 Destinasi Wisata Favorit Kabupaten/Kota Provinsi Sumatera Barat - Yolanda Febrita Wahyu; Mike Triani (Universitas Negeri Padang, 2023)
Tourism is a variety of tourism activities supported by various facilities and infrastructure provided by the community, the private sector and local government, West Sumatra Province is a national tourist destination that has various and exotic tourist objects and attractions, both natural as well as culture. The purpose of this study was to determine the effect of the number of tourist visits, the number of restaurants, and the number of hotels on employment in 9 Favorite District/City Tourism Destinations in West Sumatra Province in 2016-2021. The variables of this study consist of the dependent variable, namely employment (Y) and the independent variables, namely the number of tourist visits (X1), the number of restaurants (X2), the number of hotels (X3) and the wage rate (X4). Data collection used indirect observation techniques and the data obtained was analyzed using panel data regression. The results of the study show that there is an effect of the number of tourists on employment, there is no effect of the number of restaurants on employment, there is an effect of the number of hotels on employment, there is no effect of wage rates on employment and there is an influence on the number of tourist visits, the number of restaurants, the number hotels and wage rates on employment in 9 Favorite Tourism Destinations in West Sumatra Regency/City Province in 2016-2021.